Neuronal and hormonal regulatory mechanisms of tears production and secretion - Mrugacz, Małgorzata; Żywalewska, Nella; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The ocular surface, tear film, lacrimal glands act as a functional unit to preserve the quality of the refractive surface of the eye, and to resist injury and protect the eye against bodily and environmental conditions. Homeostasis of this functional unit involves neuronal and hormonal regulatory mechanisms. The eye appears to be a target organ for sex hormones, particulary the androgen, as they modulate the immune system and trophic functions of the lacrimal and Meibomian glands.